Behavior of a Multi-Story Steel Structure with Eccentric X-Brace - Abdulkhalik J. Abdulridha (Fracture and Structural Integrity)
Eccentrically Braced Frames (EBFs) outperform moment-resisting frames in seismically active regions because of their strength, stiffness, energy dissipation, and ductility. Conventional bracing systems, such as X, Y, V, or K types, are utilized to enhance structural integrity. This study employs computational modelling to analyze multi-story steel buildings featuring an eccentric X-brace system. In this investigation, 120 multi-story steel frame buildings were selected. These multi-story structures comprise six-, nine-, and twelve-story geometries. ETABS built a full-scale FE model of multi-story structures. The study's parametric variables are the X-brace eccentricity, steel X-brace section size, and X-braced placement. Steel X-braces may have an eccentricity of 500, 1000, or 1500 millimeters. The ETABS model was validated when its findings matched experimental data. According to the data, the eccentric X-brace increases top-story displacement more for 6-story multi-story structures than for 9- and 12-story ones. Eccentric X-braces reduced lateral stiffness, allowing more significant floor movement. Eccentric and diagonal braces offer less lateral rigidity than concentrically braced frames due to their flexibility. Eccentricity reduces stiffness, even if the X-braced component has a larger cross-section. EBFs may migrate horizontally. Since the EBF absorbs more energy, changing the X-brace section size and eccentricity affects its ductility.